ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA - NUZULA, FIRDAUSI (Jurnal Akuntansi AKUNESA, 2017)
This research aims to analyze the factors that are indicators of earnings persistence in companies listed on the Indonesia Stock Exchange 2013-2016. Indicators tested in this research are cash flow volatility, sales volatility, leverage, book tax differences, and accruals. This research used purposive sampling with total sample 2013-2016 equal to 988. The analysis method used is descriptive analysis and Confirmatory Factor Analysis (CFA). The results of this research indicate that all variables or indicators tested can be used to form the construct of earnings persistence factors. Debt level is the variable or indicator that has the greatest influence on the earnings persistence.   Keywords: earnings persistence, confirmatory factor analysis